Analisis Distribusi Biaya Proyek Menggunakan Pareto Untuk Mengidentifikasi Cost Drivers pada Proyek Revitalisasi Sekolah Rawan Banjir - Fadillah Taufik; Mardiaman Mardiaman (Jurnal Talenta Sipil, 2026)
The revitalization of school buildings in flood-prone areas has become a significant challenge in managing educational infrastructure in Indonesia. The general problem frequently encountered is the high construction cost caused by the need to adapt buildings to flood risks, while public project budgets are required to remain efficient and accountable. In the revitalization project of SDN Sukamanah 02 Jonggol, the building’s location below the surrounding road and drainage elevation resulted in recurring flooding that damaged school facilities and disrupted educational activities. The specific problem addressed in this study is the lack of information regarding project cost distribution and dominant work items (cost drivers) contributing the largest proportion of the total revitalization cost. Therefore, this study aims to analyze the cost distribution of the SDN Sukamanah 02 revitalization project using Pareto Analysis to identify dominant work items as a basis for project cost control. This research employed a descriptive quantitative method with a case study approach. The data were obtained from the Bill of Quantities (BoQ), technical specifications, field observations, and project documentation of the SDN Sukamanah 02 revitalization project. The analysis was conducted using the Pareto method by ranking work items from the highest to the lowest cost and calculating their cumulative percentage contribution to the total project cost. The results indicate that five dominant work items, namely bitumen roof covering, soil embankment, fabricated doors and windows, granite flooring, and PVC ceiling, contributed approximately 57.9% of the total project cost. These findings demonstrate that most project costs were concentrated on environmental adaptation works and architectural components. This study recommends the application of Pareto Analysis as a basis for cost control and efficiency evaluation priorities in school revitalization projects located in flood-prone areas.